2021
DOI: 10.1099/mic.0.001108
|View full text |Cite
|
Sign up to set email alerts
|

A functional menadione biosynthesis pathway is required for capsule production by Staphylococcus aureus

Abstract: Staphylococcus aureus is a major human pathogen that utilises a wide array of pathogenic and immune evasion strategies to cause disease. One immune evasion strategy, common to many bacterial pathogens, is the ability of S. aureus to produce a capsule that protects the bacteria from several aspects of the human immune system. To identify novel regulators of capsule production by S. au… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In previous work we analysed capsule production by both hemB and menD SCVs of S. aureus , where we found that those that were auxotrophic for menadione ( menD ) produced little capsule, whereas those that were auxotrophic for hemin were unaffected [20]. In this study we demonstrate that SCV associated with triclosan resistance and auxotrophic for fatty acids also produce less capsule, an effect that appears to be mediated at the transcriptional level.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…In previous work we analysed capsule production by both hemB and menD SCVs of S. aureus , where we found that those that were auxotrophic for menadione ( menD ) produced little capsule, whereas those that were auxotrophic for hemin were unaffected [20]. In this study we demonstrate that SCV associated with triclosan resistance and auxotrophic for fatty acids also produce less capsule, an effect that appears to be mediated at the transcriptional level.…”
Section: Resultsmentioning
confidence: 56%
“…In recent work we identified an association between genes associated with the SCV phenotype and capsule production [20]. We functionally verified this association and demonstrated that a menadione auxotrophic SCV did not produce capsule, whereas a hemin autotropic SCV did.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…For this reason we utilized in this study three different approaches, which allowed us to consider a wider range of loci with a focus on loci identified by more than one of the GWAS approaches. Our usual approach of functionally validating identified associations [63–67] has proven to be challenging in S. pneumoniae , as our clinical strains are highly resistant to transformation and the more genetically amenable laboratory strains do not always contain the associated gene, as we found in the case of zomB .…”
Section: Discussionmentioning
confidence: 99%